Crystal Structure of Glyceraldehyde-3-Phosphate Dehydrogenase from the Gram-Positive Bacterial Pathogen A. vaginae, an Immunoevasive Factor that Interacts with the Human C5a Anaphylatoxin - Querol-García, Javier; Fernández, Francisco J.; Marin, Ana V.; Gómez, Sara; Fullà, Daniel; Melchor-Tafur, Cecilia; Franco-Hidalgo, Virginia; Albertí, Sebastián; Juanhuix, Jordi; Rodríguez de Córdoba, Santiago; Regueiro, José R.; Vega, M. Cristina (Frontiers in Microbiology, 2017)
The Gram-positive anaerobic human pathogenic bacterium Atopobium vaginae causes most of the cases of bacterial vaginosis and opportunistic infections in immunocompromised patients. In addition to its well-established role in carbohydrate metabolism, D-glyceraldehyde-3-phosphate dehydrogenase (GAPDH) from Streptococcus pyogenes and S. pneumoniae have been reported to act as an extracellular virulence factor during streptococcal infections. Here, we report the crystal structure of GAPDH from A. vaginae (AvGAPDH) at 2.19 Å resolution. The refined model has a crystallographic Rfree of 22.6%. AvGAPDH is a homotetramer wherein each subunit is bound to a nicotinamide adenine dinucleotide (NAD+) molecule. The AvGAPDH enzyme fulfills essential glycolytic as well as moonlight (non-glycolytic) functions, both of which might be targets of chemotherapeutic intervention. We report that AvGAPDH interacts in vitro with the human C5a anaphylatoxin and inhibits C5a-specific neutrophil chemotaxis, thereby suggesting the participation of AvGAPDH in complement-targeted immunoevasion in a context of infection. The availability of high-quality structures of AvGAPDH and other homologous virulence factors from Gram-positive pathogens is critical for drug discovery programs. In this study, sequence and structural differences between AvGAPDH and related bacterial and eukaryotic GAPDH enzymes are reported in an effort to understand how to subvert the immunoevasive properties of GAPDH and evaluate the potential of AvGAPDH as a druggable target.